(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Approximately 450 million individuals worldwide suffer from mental and behavioural problems. During their lifespan, one out of every four people will acquire one or more of these diseases. Neuropsychiatric illnesses account for 13 percent of total Disability Adjusted Life Years (DALYs) lost globally due to all diseases and accidents, with that figure anticipated to climb to 15 percent by 2020. Psychiatric diseases account for five of the top 10 causes of disability and death worldwide. Mental disorders not only impose a huge psychological, social, and economic burden on society, but they also elevate the risk of physical ailments. Given the existing constraints in the effectiveness of treatment options for decreasing disability caused by mental and behavioural disorders, prevention is the only long-term strategy for minimizing the burden imposed by these diseases. The relevance of risk and protective factors in the development of mental disorders and poor mental health has been explored by social, biological, and neurological sciences. From prenatal life onwards, biological, psychological, as well as societal risk and protective factors, as well as their interactions, have been uncovered. Because many of these variables are changeable, they may be used as targets for preventive and promotion efforts. This article covers a variety of mental health topics.